Odpowiedzi

2010-02-08T19:11:25+01:00
A )2x do potegi 3 -4x +8 -x -( 2x do potęgi 2 + 5x do potęgi 2 - 4x - 3x do potęgi 2 + 15 x + 12) (3 - 2x)=2

2010-02-08T19:17:28+01:00
A)[2(x³-2x+4)-(x-3)(x²+5x-4)](3-2x)=[2x³-4x+8-(x³+5x²-4x-3x²-15x+12)] (3-2x)=
=(2x³-4x+8-x³-5x²+4x+3x²+15x-12)(3-2x)=(x³-2x²+15x-4)(3-2x)=3x³-6x²-45x-12-2x do czwartej +4x³-30x²+8x=-2x do czwartej+7x³+24x²+6x-12
b)[2(3x-4x+x³)-(2-x)(x²+6x-3)](2x-3)=[6x-8x+2x³-2x²-12x+6+x³+6x²-3x)](2x-3)=
=(3x³+4x²-17x+6)(2x-3)=6x do czwartej+8x³-34x²+12x-9x³-12x²+51x-18=6x do czwartej -x³-46x²+39x-18